1982
DOI: 10.1111/j.1399-0039.1982.tb01425.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigation in mesangial IgA nephropathy

Abstract: HLA—A, B. C. DR, MB, Bf, Gm, Am, Pi and Km genes (and 12 erythrocyte genetic systems) have been analyzed and correlated with clinical or biological features in 88 mesangial IgA glomerulonephritis. These data pointed out 2 gene frequency modifications: a significant MB1 specificity decrease in the total patient group and a significant Km I increase in the chronic renal failure mesangial IgA nephropathy subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…the decrease of MT1 and the increase of MT3 found in our patients may be in agreement with the reduction of DR2 and the increase of DR7 reported in previous studies (see references in Kirsner & Shorter 1982). There is indeed a strong association between MT and MB antigens, and DR antigens (Park et al 1980, Duquesnoy & Marrari 1980 Frequencies of HLA-DR, M T and M B antigens in 28 patients with Crohn's disease and 132 controls') Petit et al 1982, Miyanaga et al 1981, Volkman et al 1982. In our patients the gene for susceptibility to Crohn's disease appears to be associated with the MT3 gene, whereas the gene for resistance appears to be associated with the MT1 (MB1) gene.…”
supporting
confidence: 91%
“…the decrease of MT1 and the increase of MT3 found in our patients may be in agreement with the reduction of DR2 and the increase of DR7 reported in previous studies (see references in Kirsner & Shorter 1982). There is indeed a strong association between MT and MB antigens, and DR antigens (Park et al 1980, Duquesnoy & Marrari 1980 Frequencies of HLA-DR, M T and M B antigens in 28 patients with Crohn's disease and 132 controls') Petit et al 1982, Miyanaga et al 1981, Volkman et al 1982. In our patients the gene for susceptibility to Crohn's disease appears to be associated with the MT3 gene, whereas the gene for resistance appears to be associated with the MT1 (MB1) gene.…”
supporting
confidence: 91%
“…As for other genetic systems, the allotype study of the kappa light chain (Km) demonstrated a significant in crease of Km I only in the subgroup of patients with chronic renal failure [57] and the study of gamma heavy chain (Gm) showed a significant increase of one allotype, only in the subgroup presenting with macroscopic he maturia [58]. However, the majority of these studies of immunogenetics have been performed with small num bers of patients, and their results must be confirmed in larger populations to become really convincing.…”
Section: Epidemiology Geographic Distribution and Immunogeneticsmentioning
confidence: 99%
“…Furthermore, when com pared with 51 cases of IgA nephropathy diagnosed at our institution over a 5-year period, these IF findings were unique (table II). Finally, HLA phenotyping of the pa tient and father revealed the absence of BW35, BW12, and DR4 -phenotypes previously associated with IgA nephropathy [19][20]. Nor are the features of this present 51 (100) 35 (69) 22 (43) 10 (20) 47 (92) 21 (41) 1 Three to six glomeruli were studied by IF; all staining was limited to stalk or mesangial areas.…”
Section: Discussionmentioning
confidence: 99%